Role of supply chain in Cocoa Blue Print Model Performance in National development program - Nurjannah Nonci; Nurmi Nonci; Harifuddin Halim; Muliani Muliani (International Journal of Supply Chain Management, 2019)
This paper aims to reveal the application of Blue Print Model in the national cocoa movement program in Indonesia. This model compares the achievement of targets with expectations. The study was carried out by comparing targets to be achieved with targets obtained on three variables: seed rejuvenation, side-grafting activities, and intensification of cocoa plants. The results show that the target obtained is different from the expected target in the three variables. This means that the implementation of Blue Print Model in the national cocoa movement program was unsuccessful. However, with the integration of supply chain factors and blur print performance (BPP) measures, it is found that there is a significant relationship between the both. Meanwhile, some factors of supply chain have also shown their insignificant influence on the value of BPP.